Genome-wide characterization of L-aspartate oxidase genes in wheat and their potential roles in the responses to wheat disease and abiotic stresses - Feng, Yanqun; Tang, Mingshuang; Xiang, Junhui; Liu, Pingu; Wang, Youning; Chen, Wang; Fang, Zhengwu; Wang, Wenli (Frontiers in Plant Science, 2023)
L-aspartate oxidase (AO) is the first enzyme in NAD+ biosynthesis and is widely distributed in plants, animals, and microorganisms. Recently, AO family members have been reported in several plants, including Arabidopsis thaliana and Zea mays. Research on AO in these plants has revealed that AO plays important roles in plant growth, development, and biotic stresses; however, the nature and functions of AO proteins in wheat are still unclear. In this study, nine AO genes were identified in the wheat genome via sequence alignment and conserved protein domain analysis. These nine wheat AO genes (TaAOs) were distributed on chromosomes 2, 5, and 6 of sub-genomes A, B, and D. Analysis of the phylogenetic relationships, conserved motifs, and gene structure showed that the nine TaAOs were clustered into three groups, and the TaAOs in each group had similar conserved motifs and gene structure. Meanwhile, the subcellular localization analysis of transient expression mediated by Agrobacterium tumetioniens indicated that TaAO3-6D was localized to chloroplasts. Prediction of cis-elements indicated that a large number of cis-elements involved in responses to ABA, SA, and antioxidants/electrophiles, as well as photoregulatory responses, were found in TaAO promoters, which suggests that the expression of TaAOs may be regulated by these factors. Finally, transcriptome and real-time PCR analysis showed that the expression of TaAOs belonging to Group III was strongly induced in wheat infected by F. graminearum during anthesis, while the expression of TaAOs belonging to Group I was heavily suppressed. Additionally, the inducible expression of TaAOs belonging to Group III during anthesis in wheat spikelets infected by F. graminearum was repressed by ABA. Finally, expression of almost all TaAOs was induced by exposure to cold treatment. These results indicate that TaAOs may participate in the response of wheat to F. graminearum infection and cold stress, and ABA may play a negative role in this process. This study lays a foundation for further investigation of TaAO genes and provides novel insights into their biological functions.